2021
DOI: 10.1038/s41598-021-95424-6
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive recombinant human oncostatin M for NMR-based screening in drug discovery

Abstract: Oncostatin M (OSM) is a pleiotropic, interleukin-6 family inflammatory cytokine that plays an important role in inflammatory diseases, including inflammatory bowel disease, rheumatoid arthritis, and cancer progression and metastasis. Recently, elevated OSM levels have been found in the serum of COVID-19 patients in intensive care units. Multiple anti-OSM therapeutics have been investigated, but to date no OSM small molecule inhibitors are clinically available. To pursue a high-throughput screening and structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 67 publications
(119 reference statements)
0
1
0
Order By: Relevance
“…6-e ). We also found that the pathway activity of oncostatin M, the expression of which was reported to be elevated in the serum of patients with COVID-19 [35], was significantly enriched ( P < 10 − 4 ). At the same time, the most significantly upregulated gene was IL1R, the ligand of which is an important marker of severe symptoms among patients with COVID-19 [11].…”
Section: Resultsmentioning
confidence: 66%
“…6-e ). We also found that the pathway activity of oncostatin M, the expression of which was reported to be elevated in the serum of patients with COVID-19 [35], was significantly enriched ( P < 10 − 4 ). At the same time, the most significantly upregulated gene was IL1R, the ligand of which is an important marker of severe symptoms among patients with COVID-19 [11].…”
Section: Resultsmentioning
confidence: 66%
“…6-e). We also found that the pathway activity of oncostatin M, the expression of which was reported to be elevated in the serum of patients with COVID-19 [35], was significantly enriched (P < 10 −4 ). At the same time, the most significantly upregulated gene was IL1R, the ligand of which is an important marker of severe symptoms among patients with COVID-19 [11].…”
Section: Alveolar Type II Cells Colocalized With Macrophages In Sars-...mentioning
confidence: 52%
“…The compounds proposed in this patent are designed to reduce tumor cell detachment, invasion, and metastasis. Recently, a specific small molecule inhibitor named SMI-10B was characterized and shown to bind to specific amino acids within Site III of OSM via HSQC-NMR (260), and was subsequently confirmed by an independent group using molecular dynamics simulation (261). To date, this is the only patent designed for small molecule inhibition of OSM.…”
Section: Anti-osm Therapeuticsmentioning
confidence: 97%